The Effect of Residential Preferences on the Willingness to Pay for Residential with Near Toll Road Gate in Surabaya - Victor Winata Pranoto; Anastasia Njo (Dimensi Utama Teknik Sipil, 2020)
This study targeted to investigate whether factor of physical condition, planning concept offered, location, and financial affect the willingness to pay for residential with near toll road gate in Surabaya and also find out the percentage of willingness to pay for residential with near toll road gate in Surabaya. The samples are people who have intention of buying residential or have puchase residential in Surabaya and in productive age. The data analysis method used is Partial Least Square (PLS) using the Smart PLS program. The results of this analysis showed that physical condition, planning concept offered and location affect the willingess to pay for residential with near toll road gate in Surabaya, while financial not significantly affect. For willingness to pay residential with near toll road gate in Surabaya, most of them answer between 0-10%.